The Effect of Training and Work Motivation on Lecturer Performance Study at Zainul Hasan Genggong University - Ida Royani; Mudhofir Mudhofir; Fauzi Muharom; Imdad Rabbani (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The urgency of lecturers in higher education really needs to be considered because it will affect the development of the university. This can be seen from the performance of lecturers which can be obtained from how universities are able to provide education and training and are able to foster enthusiasm or work motivation in the lecturer setting. This study aims to determine the effect of the importance of training and work motivation on the performance of lecturers either partially or simultaneously. The research approach uses a quantitative approach, with 66 sample respondents from 262 Zainul Hasan Genggong University lecturers as the population. Data processing using multiple linear regression analysis. The results showed that there was a positive effect of training and work motivation partially and simultaneously, which was evidenced by the t-count results of 6.888X1 and 2.66 X2 which were positive and there was a significant effect on lecturer performance as evidenced by the coefficient of determination of 0.680 so that there is the influence of other variables of 0.320. Therefore, the higher and better the education, training and work motivation provided, the higher the performance of the lecturers shown to the college.